STUDIES ON THE EFFECT OF COLOUR OF WEBBING ON THE EFFICIENCY OF GILL NETS FOR HILSA AND POMFRET OFF VERAVEL - KUNJIPALU, K K; BOOPENDRANATH, M R; KUTTAPPAN', A C; PILLA!, N SUBRAMONIA; GOPALAKRISHNAN, K; NAIR, A. K KESAVAN (Fishery Technology, 2017)
Influence of colour of webbing on me carcn or gw ners ror commercmuy important hilsa (Hi/sa tali and Hi/sa i!isha) and pomfret ( Pampus argent?us and Parastromateus niger) has been studied in the coastal waters offVeraval. Am<mg the colours tested yellow and white are recommended for hilsa and pomfret gear. Influence of fishing depth, surface water temperature and turbidity on catch are also discussed.